Peningkatan Pengetahuan dan Keterampilan Skrining Penyakit Tidak Menular pada Kader Kesehatan POSBINDU - Imaniar Ranti (Universitas Muhammadiyah Semarang, 2022)
Non-communicable Diseases (NCDs) are rarely detected early because they are usually asymptomatic or without complaints. Some patients are usually found in an advanced stage so difficult to cure and end up with illness or premature death. One of the efforts to control PTM is to empower and increase community participation through NCDs posbindu activities with their cadres. The purpose of this Community Counseling (PKM) is to provide education and training about non-communicable diseases to health cadres in the working area of the Piyungan Health Center as partners in this PKM. This PKM uses the Active Person Learning Method (CBIA) which consists of 2 activities, namely counseling containing NCDs materials and training for NCDs early detection skills. This activity was attended by 30 cadres who were very enthusiastic during the activity. The results of the activity showed an increase in the knowledge of cadres in the good category of 80%, and 20% sufficient. The improvement of cadre skills showed good results, namely 100% of cadres were able to check vital signs and anthropometry and 70% of cadres were able to check blood sugar levels. This PKM activity was concluded to be able to increase the knowledge and skills of cadres about NCDs.